Information system use and SME characteristics in value chain activities: Evidence from the manufacturing industry in Korea - Won, Jeong Yeon; Park, Min Jae (International Journal of Value Chain Management, 2020)
This study clustered the use of information systems (ISs) of firms based on the value chain and analysed the characteristics of each cluster. The empirical analysis utilised major ISs and sample of 2,012 SMEs in the manufacturing industry. Five types of ISs use were classified as a result of clustering based on nine activities suggested in Porter's theory of competitive advantage. For these cluster types, ANOVA showed differences for all the company factors derived from the TOE framework. In particular, it revealed distinct differences in technical factors and in organisational factors. However, environmental factors did not indicate as much of difference. This study was meaningful as it analysed the main characteristics of the company in the value chain rather than just individual IS activities. It also suggests significant implications for alternative policies, such as the operation of industrial complexes and the activities they focus on under the constraints of SMEs.
Keywords: ANOVA; Cluster; Information system; Manufacture; SMEs; Value chain